2013
DOI: 10.1007/s00417-013-2529-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of false positives in retinal nerve fiber layer, optic nerve head and macular ganglion cell-inner plexiform layer from two spectral-domain optical coherence tomography devices

Abstract: Spectralis might be more specific than Cirrus when evaluating the RNFL thickness for Caucasians and moderate myopic population. GCIPL and ONH analysis might be more useful than RNFL thickness to evaluate this population using Cirrus OCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 31 publications
2
36
1
Order By: Relevance
“…Prior studies have of 2D RNFL thickness measurements have reported artifacts rates ranging from 18.0% to 46.7%. 32,4548 In the current study of 3D RNFL volume, we also found that algorithm failure in segmenting the posterior border of the RNFL was higher in OAG patients (16.9%) compared to normal patients (12.2%), and this is consistent with a previous report from our group. 32 Accurate RNFL thickness measurements are more difficult to obtain in glaucoma patients, because glaucomatous disease causes thinning of the RNFL and also loss of reflectivity of this layer.…”
Section: Discussionsupporting
confidence: 93%
“…Prior studies have of 2D RNFL thickness measurements have reported artifacts rates ranging from 18.0% to 46.7%. 32,4548 In the current study of 3D RNFL volume, we also found that algorithm failure in segmenting the posterior border of the RNFL was higher in OAG patients (16.9%) compared to normal patients (12.2%), and this is consistent with a previous report from our group. 32 Accurate RNFL thickness measurements are more difficult to obtain in glaucoma patients, because glaucomatous disease causes thinning of the RNFL and also loss of reflectivity of this layer.…”
Section: Discussionsupporting
confidence: 93%
“…[13][14][15] However, RNFL and GCIPL assessments target different neuroretinal areas, and they may be potentially complementary to overcome the incidence of false positive results of some OCT RNFL parameters. 16 Thus, in Cirrus OCT, Leal-Fonseca et al 16 reported an 11% false positive rate in the average RNFL color code and 13% in the superior and inferior quadrants and average C/D ratio. This supports the combined use of parameters from different retinal areas for diagnosing glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Axial length, mean spherical equivalent, presence of peripapillary atrophy, and tilted disc were significantly related to the RNFL FP occurrence displayed by both the devices; therefore, the degree of myopic optic disc tilt should be considered when interpreting the RNFL thickness measured by OCT 5,710. Clinical features of tilted disc overlap with other conditions, such as myopic disc and glaucoma, but the role of conventional OCT imaging technologies for the optic nerve head (ONH) is limited 4,5…”
Section: Introductionmentioning
confidence: 97%
“…A study has reported that Spectralis OCT (Heidelberg Engineering, Dossenheim, Germany) might be more specific than Cirrus (39% vs 18%) when evaluating RNFL thickness for Caucasians and moderate myopic population 5. Axial length, mean spherical equivalent, presence of peripapillary atrophy, and tilted disc were significantly related to the RNFL FP occurrence displayed by both the devices; therefore, the degree of myopic optic disc tilt should be considered when interpreting the RNFL thickness measured by OCT 5,710.…”
Section: Introductionmentioning
confidence: 99%